Proceedings of the 12th International Conference on Measurement and Quality Control - Cyber Physical Issue IMEKO TC 14 2019 - Majstorovic, Vidosav D.; Durakbasa, Numan (Lecture Notes in Mechanical Engineering,, 2019)
This book gathers the proceedings of the 12th International Conference on Measurement and Quality Control - Cyber Physical Issues (IMEKO TC 14 2019), held in Belgrade, Serbia, on 4-7 June 2019. The event marks the latest in a series of high-level conferences that bring together experts from academia and industry to exchange knowledge, ideas, experiences, research findings, and information in the field of measurement of geometrical quantities. The book addresses a wide range of topics, including: 3D measurement of GPS characteristics, measurement of gears and threads, measurement of roughness, micro- and nano-metrology, laser metrology for precision measurements, cyber physical metrology, optical measurement techniques, industrial computed tomography, multisensor techniques, intelligent measurement systems, evaluating measurement uncertainty, dimensional management in industry, product quality assurance methods, and big data analytics. By providing updates on key issues and highlighting recent advances in measurement and quality control, the book supports the transfer of vital knowledge to the next generation of academics and practitioners.